2016
DOI: 10.2139/ssrn.2722482
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Innovation and Globalization Strategies in Post-Crisis Recovery

Abstract: THE ROLE OF INNOVATION AND GLOBALIZATION STRATEGIES IN POST-CRISIS RECOVERY 3The aim of the research is to conduct an empirical investigation and reveal what types of globalization and innovation strategies in turbulent and unfavorable regional institutional environment are most likely to be associated with different trajectories of Russian manufacturing firms' performance in 2007-2012. We employ the results of empirical survey of 1000 medium and large enterprises in manufacturing ( 2009) linked to financial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Finally, operating in high-tech industries leads to higher levels of performance, which is a finding that more or less corroborates with evidence presented in other studies based on Russian samples (e.g. Golikova et al , 2012; Golikova and Kuznetsov, 2016). Other firm- and industry-specific issues, such as age, industry concentration and industry-based technological intensity, had no impact on performance in both models.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Finally, operating in high-tech industries leads to higher levels of performance, which is a finding that more or less corroborates with evidence presented in other studies based on Russian samples (e.g. Golikova et al , 2012; Golikova and Kuznetsov, 2016). Other firm- and industry-specific issues, such as age, industry concentration and industry-based technological intensity, had no impact on performance in both models.…”
Section: Resultssupporting
confidence: 89%
“…As Russian exporting companies do not have enough resources (on average) allowing them to outperform their local counterparts, they need additional resources as they mainly operate in very traditional and low-tech industries. Damijan et al (2013), Du et al (2012), and Lin et al (2014) for Chinese listed companies obtained similar results, whereas Filatotchev et al (2008) and Golikova and Kuznetsov (2016) confirmed the opposite hypothesis. In line with Fedorova et al (2015), we can conclude that there are some additional company characteristics, which a firm should have if it is to benefit from internalization.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Foreign-owned firms can overcome the entry barriers to foreign markets. Foreign capital from developed countries has the opportunity to apply more advanced technology in the firms and use it to create new competitive products (Golikova & Kuznetsov, 2016). Technology acquisition from developed countries led to innovation and learning processes in developing countries which were the main source of export excellence at the firm level (Belitz & Mölders, 2016).…”
Section: Introductionmentioning
confidence: 99%